ChemInform Abstract: Palladium‐Catalyzed Arylation of 2H‐Chromene: A New Entry to Pyrano[2, 3‐c]carbazoles. Issue 3 (29th December 2015) - Ranjith Reddy, K.; Siva Reddy, A.; Dhaked, Devendra K.; Rasheed, S. K.; Pathania, Anup Singh; Shankar, Ravi; Malik, Fayaz; Das, Parthasarathi
Abstract: Suzuki—Miyaura cross‐coupling of (het)arylboronic acids with chromene derivative (I) provides the corresponding 5‐(het)arylated chromenes that can be subjected to Cadogan reaction to give the title compounds.